The influence pattern of scale effect on coarse-grained soil particle breakage: an experimental study - Li, Xia; Du, Jun; Shen, Xinggang; Wang, Chenghan; Liu, Yubo; Jin, Haoran; Jiang, Mingjie (Frontiers in Materials, 2025)
Coarse-grained soil is a common material for earth-rock dams and soft-ground projects. However, such soil particles are prone to breakage under load, thus affecting project safety. Accurately understanding the particle breakage characteristics is crucial to the safety design of related projects. Due to the scale effect, the indoor test results of scaled soil materials often fail to effectively reflect the breakage of coarse-grained soil particles with the original gradation. According to previous studies, the scale effect of scaled soil materials is mainly affected by the maximum particle diameter Dmax and the gradation structure. Among them, the gradation structure can be represented by the gradation area S. By changing the gradation area S and the maximum particle diameter Dmax, 39 coarse-grained soil specimens with the same relative compaction were prepared for loading tests on a large-scale triaxial coarse-grained soil test system. The indices Bw and Bg were developed to quantitatively analyze the scale effect’s influence on coarse-grained soil particle breakage, with a focus on identifying strategies to mitigate this scale effect. The test results show the following findings: Maintaining a constant maximum particle diameter, the indices Bw and Bg for particle breakage show a decrease as the gradation area enlarges, revealing a logarithmic correlation. Conversely, with a stable gradation area, these indices, Bw and Bg, rise as the maximum particle diameter increases, indicating an exponential relationship. The experimental findings led to the development of a scale effect-based calculation model for Bw and Bg using the similar gradation approach, whose accuracy has been confirmed. Furthermore, a prediction technique for the breakage degree of original-gradation coarse-grained soil under specific confining pressure was formulated using indoor test data, potentially enhancing project design safety. In the design of earth-rock dams, the research results can be used to more accurately predict the degree of particle breakage of coarse-grained soil with the original gradation. This can optimize the design of the dam body structure and improve the safety of the project.